Improvement of the Functional Properties of Bread and Bake Products (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
A review of the literature on the production of bakery products is presented. Problems tasks promising directions of development of the industry as well as the use of whey in the production of bread are considered.